(untitled) (American International Journal of Business and Management Studies, 2021)
The aim of this study is to investigate the effects of human capital attributes on the employability readiness of the engineering graduates of the High Education Institutes in Oman. The study adopted self-directed structured questionnaire distributed to a sample of engineering students and graduates from a number of colleges and universities. The study used the structural equation modelling (SEM) for analysing the collected data. The findings of the statistical analysis of the study showed that Omani graduates signify professional ethics and morality, teamwork including respecting others, cooperating, negotiating, persuading, and contributing to discussions, Communication skills including listening and questioning, Capacity for lifelong learning including openness to new ideas, Creative thinking of the ability to develop and apply appropriate solutions, and Problem solving skills of the ability to analyse facts and situations as the top required skills of Readiness for Employability. Specifically, study findings showed Human capital attributes factor has high influence on the Readiness for Employability of the graduates in Oman. Finally, the study’s implementations and recommendations could be transferred to the Gulf and Arab or other countries’ contexts having similar settings of HE systems and similar issues of skills gap and employability concern of their graduates.